PHYTOSTEROLS, A TRITERPENOID, AND A LONG CHAIN ALCOHOL ISOLATED FROM THE LEAVES OF Camellia dalatensis Luong, Tran & Hakoda - Nguyễn Thị Tố Uyên; Trần Thị Thanh Phúc; Lương Văn Dũng; Trịnh Thị Điệp (Tạp chí Khoa học Đại học Đà Lạt)
By various chromatographic methods, five compounds including spinasterol, stigmasterol,  oleanolic acid, docosane, and 1-tricosanol were isolated from the ethanol extract of the leaves of Camellia dalatensis Luong, Tran, & Hakoda. Their structures were elucidated by extensive spectroscopic methods including 1D-NMR, 2D-NMR, ESI-MS, and IR. This is the first report of these compounds from this species.